Inherited Immunodeficiencies With High Predisposition to Epstein–Barr Virus-Driven Lymphoproliferative Diseases - Latour, Sylvain; Winter, Sarah (Frontiers in Immunology, 2018)
Epstein-Barr Virus (EBV) is a gamma-herpes virus that infects 90% of humans without any symptoms in most cases, but has an oncogenic potential, especially in immunocompromised individuals. In the past 30 years several primary immunodeficiencies (PIDs) associated with a high risk to develop EBV-associated lymphoproliferative disorders, essentially consisting of virus-associated hemophagocytic syndrome (VAHS), non-malignant and malignant B-cell lymphoproliferative disorders (LPD) including non-Hodgkin and Hodgkin’s types of B lymphomas have been characterized. Among them are SH2D1A (SAP), XIAP, ITK, MAGT1, CD27, CD70, CTPS1, RASGRP1 and CORO1A deficiencies. Penetrance of EBV infection ranges from 50 to 100% in those PIDs. Description of large cohorts and case reports have refined the specific phenotypes associated to these PIDs helping to the diagnosis. Specific pathways required for protective immunity to EBV have emerged from studies of these PIDs. SAP-dependent SLAM receptors and MAGT1-dependent NKG2D pathways are important for T and NK-cell cytotoxicity towards EBV-infected B-cells, while CD27-CD70 interactions are critical to drive the expansion of EBV-specific T-cells. CTPS1 and RASGRP1 deficiencies further strengthen that T-lymphocyte expansion is a key step in the immune response to EBV. These pathways appear to be also important for the anti-tumoral immune surveillance of abnormal B cells. Monogenic PIDs should be thus considered in case of any EBV-associated lymphoproliferative disorders.